Nexus between Artificial Intelligence and renewable energy generation in China: The role of green finance - Chan, Jason Jin Yung; Koay, Zhi Jie; Ng, Kai En (2025)
The global transition towards renewable energy has gained significant attention in recent years, with China emerging as the biggest producer of renewable energy. However, past research has yet to acknowledge the significance of artificial intelligence on advancing the renewable energy generation. This paper discusses the significance of artificial intelligence in facilitating renewable energy generation and the mediating and moderating role of green finance based on China annual data from 1992-2021. This research incorporated Autoregressive Distribute Lag Model (ARDL) to examine for the existence of mediating and moderating role of green finance in the long run and synergistic effect of green finance and artificial intelligence. This study highlights the following key finding. First, there is long run relationship between green finance on the relationship between artificial intelligence and renewable energy generation. Second, green finance has a partial mediating effect of green finance on the relationship between artificial intelligence and renewable energy generation. Third, green finance plays an effective moderating role in the nexus between artificial intelligence and renewable energy generation. These findings inspire us to propose policy implications for China should strength its position in the renewable energy generation through promoting green finance and integrating artificial intelligence.